Potential Trichoderma sp. from Peat Soil in Controlling Seed-Borne Pathogens and Growth Stimulator in Soybean (Glycine max L.) - Diasi, Ananta Rizki; Purnawati, Arika; Wiyatiningsih, Sri (BIOEDUSCIENCE, 2024)
Background: Seed-borne pathogens threaten plants because they can survive in seed tissues for long periods. Efforts that can be made include treating the seeds before planting them in the field with biological agents, one of which is Trichoderma sp. It is often found in soil with high organic matter, namely peat soil. This research aims to determine the potential of Trichoderma sp. isolates. from peat soil on pathogen infection of soybean seeds and germination of soybean seeds. Method: This research used a factorial method. The first factor was sick and healthy seeds, and the second was Trichoderma sp. isolates, consisting of TP1 and TP2. The control treatment uses the active ingredient fungicide mancozeb 80%. Seed treatment was carried out by soaking the seeds in a suspension of Trichoderma sp. with a spore density of 106 for 24 hours. The seeds were then tested using the growing-on-test method in sterile soil. Results: Identifying pathogens in soybean seeds found two genera, Aspergillus sp., and Fusarium sp., in the immersion treatment on Trichoderma sp isolates. TP2 gave the best results, where the lowest infection power was 46.6% for healthy seeds and 73.3% for symptomatic seeds. In addition, treatment with isolates of Trichoderma sp. TP2 can increase the germination capacity of soybean seeds by 60.0%. However, seed treatment with Trichoderma sp. does not affect soybean plant height and root length growth. Conclusion: The two isolates of Trichoderma sp. from peat soil positively protect seeds against soybean seed pathogens, seed germination, and soybean growth.